Carrying Out Website Security Analysis Using the Standard Penetration Testing Method - Sari, Dhea Permatas; Pakaja, Fachrudin (International Journal of Multidisciplinary Applied and Science Research, 2024)
The high level of cybersecurity threats such as SQL injection attacks, cross-site scripting (XSS), and data breaches makes website security testing a critical need. This study aims to analyze website security vulnerabilities using the PTES method as a comprehensive penetration standard. The study uses an exploratory qualitative approach with five PTES stages: (1) pre-engagement, (2) intelligence gathering, (3) vulnerability analysis, (4) exploitation, (5) post-exploitation and maintaining access. The results of the study revealed that the SPPT Online website in Mojokerto City that had been scanned provided several accesses to open protocols created for communication channels. PTES effectively uncovered multidimensional vulnerabilities with a structured approach. The results of the study can be a guide to improving website security posture, especially in the financial management sector. This study highlights the urgency of periodic security audits based on standards such as PTES to mitigate cyber risks.